Cognitive, Behavioral, and Sensory Profile of Pallister–Killian Syndrome: A Prospective Study of 22 Individuals - Fetta, Anna; Soliani, Luca; Trevisan, Alessia; Pugliano, Rosa; Ricci, Emilia; Di Pisa, Veronica; Pignataro, Veronica; Angotti, Marida; Rocca, Alessandro; Salce, Bianca; Mancardi, Maria Margherita; Giordano, Lucio; et al. (Genes, 2022)
Background: Developmental delay and intellectual disability are two pivotal elements of the phenotype of Pallister–Killian Syndrome (PKS). Our study aims to define the cognitive, adaptive, behavioral, and sensory profile of these patients and to evaluate possible correlations between the different aspects investigated and with the main clinical and demographic variables. Methods: Individuals of any age with genetically confirmed PKS were recruited. Those ≤ 42 months were administered the Bayley Scales of Infant and Toddler Development Third Edition (Bayley-III), and those > 42 months the Vineland Adaptive Behavior Scales—Second Edition (Vineland-II). Stereotyped behaviors (Stereotypy Severity Scale, SSS) and aggressive behaviors (Behavior Problems Inventory—Short Version, BPIs) were assessed in all subjects > 1 year; sensory profile (Child Sensory Profile 2, C-SP2) in all aged 2–18 years. Results: Twenty-two subjects were enrolled (11 F/11 M; age 9 months to 28 years). All subjects ≤ 42 months had psychomotor developmental delay. Of the subjects > 42 months, 15 had low IQ deviation, and 1 in the normal range. Stereotypies were frequent (median SSS-total score 25/68). Lower Vineland-II values corresponded to greater intensity and frequency of stereotypies (p = 0.004 and p = 0.003), and self-injurious behaviors (p = 0.002 and p = 0.002). Patients with severe low vision had greater interference of stereotypies (p = 0.027), and frequency and severity of aggressive behaviors (p = 0.026; p = 0.032). The C-SP2, while not homogeneous across subjects, showed prevalence of low registration and sensory seeking profiles and hypersensitivity to tactile and auditory stimuli. Lower Vineland-II scores correlated with higher Registration scores (p = 0.041), while stereotypies were more frequent and severe in case of high auditory sensitivity (p = 0.019; p = 0.007). Finally, greater sleep impairment correlated with stereotypies and self-injurious behaviors, and lower Vineland-II scores. Conclusions: The present study provides a further step in the investigation of the etiopathogenesis of the syndrome. Furthermore, these aspects could guide rehabilitation therapy through the identification of targeted protocols.